Manajemen Konflik Berbasis Komunitas: Studi Kasus Community Oriented Policing (COP) di Malioboro Yogyakarta - Zuhdan, Muhammad (Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
The purpose of this paper want to see how the concept of Community Oriented Policing (COP) applied to manage conflict in the public sphere with capital intensive , multi-actor and multi-interest. This paper offers the idea that COP could be an ideal mirror to applied policing in order to manage conflict within the framework of human rights, democracy, and local wisdom. COP becomes reflection of transforming conflict management and creating social order in public sphere, from State-Based Approach to Community-Based Approach. Furthermore, mobilization of community social capital becomes an important variable in conflict management undertaken by the COP. The method of this research is descriptive qualitative, that held on which July 2006 â July 2007. COP in Malioboro Yogyakarta is the object. Using conceptual framework based on cutting-edge and in-depth research findings , this paper built into a scientific narrative praxis.